814 Outcome of Children Admitted to a Regional Paediatric Intensive Care Unit (PICU) with Convulsive Status Epilepticus (CSE). (October 2012) - Jayachandran, S; Ramesh, P; Kumar, R
Abstract : Background and Aims: Children presenting with CSE are commonly referred to PICU for ongoing care. Limited data is available on their outcome. Objectives: To determine mortality and short-term morbidity of children admitted to a regional PICU with CSE. To identify differences in outcome for those with pre-existing epilepsy compared to non-epileptics. Methods: A retrospective cohort study of 57 children (1 month to 16 years) admitted to a regional PICU between January 2008 and December 2011 with CSE was carried out. Study population were divided into Group 1 (n=23, presence of pre-existing epilepsy) and Group 2 (n=34, absence of pre-existing epilepsy). Results: The results of the group 1 and 2 respectively were: Median age (months): 33 and 21.5 Male: female ratio (%): 57:43 and 76:24 Refractory seizures (>60 min) at presentation: 83% and 53% Deviation from APLS protocol for seizure control: 43% and 32% Extra doses of benzodiazepine: 50% and 91% Neurological co-morbidity:91% and 24% Median duration of PICU ventilation:18.1 hrs and 10.5 hrs Median duration of PICU stay:24.1 and 24.5 hrs Seizure control at PICU admission: 61% and 94% Midazolam infusion in PICU: 96% and 97% Neurological investigations (LP, CT/MRI Head, EEG) performed in 22% and 94% Pre-discharge neurological morbidity: 2 (aggressive behaviour, decerebrate posturing) and 1 (increased tone) No mortality identified Conclusion: Epileptics presented frequently with refractory seizures and were ventilated longer though this didn't affect total PICU stay; non-epileptics were investigated more frequently. Morbidity (5%) was still seen though there was no mortality in our study.